E-servant: an intelligent, programmable system to support and integrate assisted living technologies - Picking, Richard; Grout, Vic; Casas, Roberto; Blasco, Ruben (Healthcare technology letters, 2014)
The ‘E-servant’, a programmable system to control and manage assistive technologies, telehealth and telecare devices in a home environment is presented. The E-servant is programmed using a simple graphical interface that allows the user to build a dialogue in the form of a production rule system, which is triggered by a patient- or technology-initiated event. The patient interacts with the system through a personalised user interface to reach their goal of completing a task. These tasks, which the authors call ‘scenarios’, can be designed for users of different abilities (cognitive and/or physical). They can also be given priority levels, for example if a potential emergency situation arises in the patient's home, a scenario associated with the sensing of this event takes highest priority. The research presented in this Letter outlines the E-servant, its programming tool and reports its evaluation in living laboratory settings. The results suggest that it can be used as a central management system for supporting an integrated support environment for facilitating healthcare and activities of daily living, especially for older patients.